2011
DOI: 10.1073/pnas.1111053108
|View full text |Cite
|
Sign up to set email alerts
|

CD146, an epithelial-mesenchymal transition inducer, is associated with triple-negative breast cancer

Abstract: The epithelial-mesenchymal transition (EMT) plays an important role in breast cancer metastasis, especially in the most aggressive and lethal subtype, "triple-negative breast cancer" (TNBC). Here, we report that CD146 is a unique activator of EMTs and significantly correlates with TNBC. In epithelial breast cancer cells, overexpression of CD146 down-regulated epithelial markers and up-regulated mesenchymal markers, significantly promoted cell migration and invasion, and induced cancer stem cell-like properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
193
5
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(221 citation statements)
references
References 30 publications
16
193
5
7
Order By: Relevance
“…It was shown that CD106 protein was expressed only on MSCs but not on fibroblasts (10). CD146 (also known as melanoma cell adhesion molecule MCAM) is important for endothelial cell migration and angiogenesis (15). It was shown that only 4.83% of fibroblasts were CD146 positive compared with MSCs of early (91.7%) and late (79.8%) passages (10).…”
Section: Differences Between Mesenchymal Stem Cells and Fibroblastsmentioning
confidence: 99%
“…It was shown that CD106 protein was expressed only on MSCs but not on fibroblasts (10). CD146 (also known as melanoma cell adhesion molecule MCAM) is important for endothelial cell migration and angiogenesis (15). It was shown that only 4.83% of fibroblasts were CD146 positive compared with MSCs of early (91.7%) and late (79.8%) passages (10).…”
Section: Differences Between Mesenchymal Stem Cells and Fibroblastsmentioning
confidence: 99%
“…recently, induction of epithelial-mesenchymal transition (EMT), has also been documented (7,8). Despite the copious body of data describing the expression of CD146 in a myriad of cancers, noninvasive in vivo molecular imaging of CD146 expression has remained unexplored.…”
mentioning
confidence: 99%
“…CD146 was first identified as a marker for melanoma progression 13 . Later on, CD146 was also identified as a factor in angiogenesis, and tumour cell invasion and migration [14][15][16][17] . We have previously reported that CD146 regulates cell migration through cytoskeleton proteins by activating the small GTPase RhoA 18 .…”
mentioning
confidence: 99%
“…These results strongly suggest that CD146 is a negative regulator of canonical Wnt signalling at the b-catenin level. Although CD146 has been extensively studied in tumour metastasis, invasion and angiogenesis, its ligand is still under investigation 16,[32][33][34] . As a non-canonical Wnt ligand, Wnt5a has a critical role in regulating cell motility, cell polarity and CE during embryo gastrulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation